Scalable continuous evolution for the generation of diverse enzyme variants encompassing promiscuous activities - Gordon Rix (Nature Portfolio, 2020)
Generating rich ortholog diversity for biocatalysts can be difficult due to the deep evolutionary processes involved. Here the authors use OrthoRep to rapidly evolve TrpB to produce sequence-diverse variants with altered substrate promiscuity.